Des milieux partenaires en formation pratique à l’enseignement professionnel : représentations des rôles des accompagnants - Andréanne Gagné; Andréanne L. Nolin (Questions Vives)
Various partners are mobilized to accompany the student-teacher during their bachelor’s degree in the context of their internships in professional training. Gagné (2019) notes that there is confusion about the roles of the different actors involved in the professional training environment. This research explores the roles of the different partners in vocational education support in relation to a structuralist approach of representations by Abric (2011). Twenty-four actors in the professional training setting participated in semi-structured interviews and the results of this article are drawn from phase two regarding the partnership schema. Respondents reach a consensus regarding the formal roles in accompanying the student-teacher. For the informal roles and the ambiguous role, each respondent had their own view based on their experience in teacher-training. The conclusions of this article indicate that the environments accompanying the intern are more or less partners and the actors do not have a clear vision of this partnership to accompany the student-teacher. A better delimitation of roles would therefore allow for better accompaniment of student teachers in professional training.